A Case of Vasa Previa Diagnosed at Term: Elective Caesarean Section with Good Feto-Maternal Outcomes - Nathania N; Gurnadi JI; Rinaldi A; Rahmanita T (International Medical Case Reports Journal)
Nathania Nathania,1 Jeffry Iman Gurnadi,2 Andi Rinaldi,1 Triana Rahmanita1 1Department of Obstetrics and Gynecology, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Obstetrics and Gynecology, Cibabat District Hospital, Cimahi, IndonesiaCorrespondence: Nathania Nathania, Email nathania21004@mail.unpad.ac.idAbstract: Vasa previa is a condition where unprotected fetal vessels, neither by placenta nor umbilical cord, lie within the membranes over the internal cervical ostium and beneath the presenting part of the fetus. Due to this condition, the membranous vessels pose a higher risk of being compressed or ruptures and could lead to fetal demise, exsanguination, or even fetal death. In this case report, we reported a case of a 36-year-old woman, G3P2A0, at term gestation and oblique lie. Early prenatal diagnosis using transvaginal ultrasound could increase the survival rate of the fetus if followed by sufficient management after diagnosis. Caesarean birth is the safest mode of delivery even before the clinical signs or onset of labor occur.Keywords: vasa previa, early diagnosis, caesarean section